2008
DOI: 10.3928/00220124-20080701-07
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing Nurse-Physician Collaboration Using Pediatric Simulation

Abstract: The results of this study hold promise for this critical area of science that seeks to improve the outcomes of patients who experience life-threatening events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…In the past ten years, teaching and learning strategies adapted from crew resource management have led to development of a new focus in medical education. Called crisis resource management (CRM) in the healthcare industry (Flanagan, Nestel, & Joseph, 2004;Messmer, 2008;Nickerson, Morrison, & Pollard, 2011;Rudy et al, 2007;Van de Ven et al, 2010), this training methodology has the potential to reduce adverse outcomes and lead to greater collaboration and teamwork in patient care (Messmer, 2008).…”
Section: While Numbers and Percentages Vary It Is Estimated That A Vmentioning
confidence: 99%
“…In the past ten years, teaching and learning strategies adapted from crew resource management have led to development of a new focus in medical education. Called crisis resource management (CRM) in the healthcare industry (Flanagan, Nestel, & Joseph, 2004;Messmer, 2008;Nickerson, Morrison, & Pollard, 2011;Rudy et al, 2007;Van de Ven et al, 2010), this training methodology has the potential to reduce adverse outcomes and lead to greater collaboration and teamwork in patient care (Messmer, 2008).…”
Section: While Numbers and Percentages Vary It Is Estimated That A Vmentioning
confidence: 99%
“…Findings of the study showed that with more simulation exposures, physician-nurse collaboration significantly improved where both parties treated each other with greater respect and trust. Deeper understanding and insights into each others' roles and responsibilities were also achieved (Messmer, 2008).…”
Section: Recommendations To Improve Physician-nurse Collaborationmentioning
confidence: 99%
“…Another recommendation is the conduct of simulation exercises at TDCHI. This recommendation is anchored on several studies including that of Messmer (2008) who conducted an inter-professional simulation program in a children's hospital. In the study, physicians and nurses were exposed to three different life-threatening simulated situations and their performances and interactions were observed and scored.…”
Section: Recommendations To Improve Physician-nurse Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…One study by Messmer 15 examined how the use of pediatric simulation involving three scenarios enhanced nursephysician collaboration. Results of her study indicated that with each scenario pediatric nurses and residents communicated more with each other and "appeared to become more collegial toward each other, recognizing the strengths that each group brought to the team."…”
Section: Background Pediatric Simulation In Interprofessional Educatimentioning
confidence: 99%